Job Crafting and Performance in Firefighters: The Role of Work Meaning and Work Engagement - Dan, Cristina-Ioana; Roşca, Andra Cǎtǎlina; Mateizer, Alexandru (Frontiers in Psychology, 2020)
The Job Demands-Resources (JD-R) model was often utilized as an explanatory framework when investigating the strain process among first responders in general and firefighters in particular. Yet, little is known about the motivational processes whithin firefighters. The aim of this study is to expand the knowledge regarding the motivational process of firefighters by investigating job crafting and introducing work meaning within the motivational framework of the JD-R model, in relation to job performance. A cross-sectional survey design was used to collect data from one sample consisting of Romanian firefighters (n = 1,151). Structural equation modeling indicated the existence of both a direct and an indirect effect between job crafting and job performance through work meaning and work engagement. Our findings suggest that firefighters actively engage in job crafting behaviors and also that work meaning can be an outcome of job crafting. Results also encourage further research related to the way work meaning impacts job performance, through its link with work engagement. This study raises attention on how Fire departments may be able to create a climate that emphasizes meaningfulness and engagement, together with opportunities toward job redesign and a focus process based on efficiency gain.